Innovation Capacity as a Governance Mechanism in Advancing Inclusive and Adaptive Public Service Systems - Ali Anas; Ade Fery Afrisal; Batara Surya; Nurhaedah Nurhaedah (Universitas Teuku Umar, 2026)
This study examines the role of innovation capacity within inclusive public service governance by developing an integrative analytical framework. Existing literature on public sector innovation, collaborative governance, and digital transformation remains conceptually fragmented, with limited attention to how innovation capacity connects these domains. To address this gap, the study adopts a qualitative analytical approach supported by bibliometric mapping using VOSviewer to explore thematic structures and relationships within the literature. The findings indicate that innovation capacity occupies a central yet under-theorized position in governance discourse. It operates across institutional, relational, and systemic levels, enabling the integration of multi-actor collaboration, digital infrastructures, and adaptive service design. Rather than functioning solely as an organizational capability, innovation capacity emerges as a governance mechanism that transforms fragmented processes into coherent and outcome-oriented public service systems. This study contributes by reframing innovation capacity as a multi-level governance mechanism that bridges collaboration, digitalization, and inclusivity. The findings highlight the importance of systemic capacity building, emphasizing institutional coordination, digital integration, and stakeholder engagement. While limited by its reliance on bibliometric analysis, the study provides a foundation for future empirical research on innovation capacity in diverse governance contexts.